نسبة مساهمة القدرة اللاهوائية لاداء مهارتي التصويب من القفز والمناولة الطويلة للاعبات كرة السلة فئة الشابات - نوري, فيصل غازي; محمد, اياد نورالدين (Sulaimani Journal for Humanities, 2018)
Search aimed to identify the: The relationship between anaerobic ability to perform the my skills corrigendum of the long jump and handling the research sample, and the percentage contribution of anaerobic ability to perform the my skills Corrigendum of the long jump and handling the research sample. The imposition of the research included that there were statistically significant differences between the anaerobic ability to perform the my skills Corrigendum of the long jump and handling the research sample relationship and contribute to the anaerobic capacity in different proportions in the performance of my skills Corrigendum of the long jump and handling , And that the nature of the study necessitated the two researchers using descriptive method survey manner and a linking. Included research society players clubs Sulaimaniyah province and posts in the governorate championship for the sports season 2014 - 2015 basketball young category of their number (54) player. The research sample has included players clubs Sulaimaniyah province posts in the governorate League basketball for young women and of their number (40) for the player and as a percentage (74.074%) and of clubs (Sulaymaniyah Sirwan Noi -afreudat - Darbandikan). And adopted two researchers to a number of data-collection methods, including anaerobic tests in addition to offensive skills basketball tests have been using a range of instruments and tools have been conducting exploratory experience of the tests to identify the problems and negatives that may face two researchers during the main trial and after making sure been a major experiment which apply tests under discussion since the researcher with the Assistant team division of tests over two days for each team , And has processing data using some statistical methods depending on statistical the bag (SPSS) was reached important conclusions and recommendations of which there is a positive correlation moral relationship between anaerobic power (Allaktekah) with the skill of scoring by jumping after clapotement , There were no significant correlation between the anaerobic capacity (anaerobic Vosagiina) with long-handling skill, The most important recommendations need to conduct functional tests and considered a fundamental criterion to improve the health situation and confirm the training programs that contribute to the skill performance and work on their development and development of safety.